A Review of Robotic Mitral Valve Surgery. Issue 2 (4th March 2021) - Hamandi, Mohanad; Hafen, Lee; Squiers, John J.; Lanfear, Allison T.; DiMaio, J. Michael; Smith, Robert L.
ABSTRACT: Robotic mitral valve surgery is the next step in the evolution of minimally invasive mitral valve surgery. Although robotic mitral valve surgery shares many of the advantages of the traditional minimally invasive approach, it has not been widely accepted due to persistent concerns regarding cost and other issues related to patient outcomes. We reviewed literature to explore the concerns limiting proliferation of robotic mitral valve surgery; herein we aim to describe the outcomes, durability, and cost effectiveness of the robotic approach. Abbreviations: ASD: Atrial septal defect; CBP: cardiopulmonary bypass; CT: computed tomography; MR: mitral regurgitation; MV: mitral valve; PFO: patent foramen ovale; QOL: quality of life.